City spies - Ponti, James (Aladdin, 2020)
"Sara Martinez is facing years in the juvenile detention system for hacking into the foster care computer system to prove that her foster parents are crooks. But then she gets a second chance when a mysterious man offers her a chance to join a group of MI6 affiliated spies"--